2011
DOI: 10.1152/ajpcell.00076.2011
|View full text |Cite
|
Sign up to set email alerts
|

Aldosterone stimulates vacuolar H+-ATPase activity in renal acid-secretory intercalated cells mainly via a protein kinase C-dependent pathway

Abstract: Urinary acidification in the collecting duct is mediated by the activity of H(+)-ATPases and is stimulated by various factors including angiotensin II and aldosterone. Classically, aldosterone effects are mediated via the mineralocorticoid receptor. Recently, we demonstrated a nongenomic stimulatory effect of aldosterone on H(+)-ATPase activity in acid-secretory intercalated cells of isolated mouse outer medullary collecting ducts (OMCD). Here we investigated the intracellular signaling cascade mediating this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
39
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 71 publications
(88 reference statements)
2
39
0
Order By: Relevance
“…Both our in vivo and in vitro data demonstrate that effectors of the PKA (cpt-cAMP) and PKC (DOG) pathways mimic the effect of aldosterone on caput clear cell activity. These results are in agreement with our previous studies showing activation of V-ATPase-dependent proton secretion in renal intercalated cells by these agonists (63). Previous results from our group have also shown that luminal delivery of drugs that stimulate either the PKA or PKC pathways increase clear cell activity (6,40).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Both our in vivo and in vitro data demonstrate that effectors of the PKA (cpt-cAMP) and PKC (DOG) pathways mimic the effect of aldosterone on caput clear cell activity. These results are in agreement with our previous studies showing activation of V-ATPase-dependent proton secretion in renal intercalated cells by these agonists (63). Previous results from our group have also shown that luminal delivery of drugs that stimulate either the PKA or PKC pathways increase clear cell activity (6,40).…”
Section: Discussionsupporting
confidence: 93%
“…These results indicate an amplification of the amount of V-ATPase present at the cell surface via either activation of the exocytosis of V-ATPase-rich vesicles or via inhibition of endocytosis. As a positive control we also analyzed sections from the kidney of mice treated with aldosterone, cpt-cAMP, or DOG and observed increased V-ATPase-rich microvilli projections in intercalated cells (data not shown), similar to our recently published observations (43,63). In addition to being regulated via recycling mechanisms, previous studies conducted mainly in yeast and insects have shown that V-ATPase activity can also be regulated via local assembly/disassembly of V-ATPase subunits (12,30,57).…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations